Intrahepatic cholestasis occurring with prurigo of pregnancy. - Cicek, Demet; Kandi, Basak; Demir, Betul; Turgut, Dilara (My University, 2007)
A 23-year-old woman presented to our polyclinic complaining of itching, generalized dermatitis, and jaundice. She was in her 31st gestational week and had developed pruritus and the dermatitis since the first month of pregnancy; her jaundice started about a month before presentation. Her history included similar complaints in a previous pregnancy, which resulted in premature birth of a baby with a permanent brain defect. One of her sisters had had jaundice and itching in her 27th gestational week and delivered a healthy baby; a second sister had experienced itching and dermatitis in her second trimester and delivered a healthy baby. Physical examination of the patient showed that her eyes were jaundiced (Figure 1); skin examination revealed generalized erythematous excoriated papules, symmetrically distributed all over her body (Figure 2 Figure 3). Laboratory analyses revealed the following results: leukocyte count, 14.30/mm(3) (3.8-10.3/mm(3)); erythrocyte sedimentation rate, 25 mm/h (<20 mm/h); aspartate aminotransferase, 44 U/L (5-40 U/L); alanine aminotransferase, 63 U/L (5-40 U/L); lactate dehydrogenase, 1158 U/L (220-450 U/L); total bilirubin, 6.88 mg/dL (<1.10 mg/dL); and direct bilirubin, 3.27 mg/dL (<0.35 mg/dL). Urinalysis results were positive for bilirubin and urobilinogen. Positive serologic findings included rubella immunoglobulin G, 93 AU/mL (<15) and cytomegalovirus, 188 AU/mL (<10); negative findings included herpes simplex virus type 2 and hepatitis. Histopathologic examination of material collected from the left breast via punch biopsy showed parakeratosis, acanthosis, and perivascular lymphocyte infiltration in dermal vessels. Treatment with 2 g/d cholestyramine and a topical corticosteroid was effective in the patient, who was diagnosed with intrahepatic cholestasis of pregnancy and prurigo of pregnancy based on the clinical, histopathologic, and laboratory findings. To the authors' knowledge, this is the first such reported case in the literature.
Keywords: Adult; Cholestasis, Intrahepatic; Dermatitis; Female; Humans; Pregnancy; Pregnancy Complications; Pruritus; adult; case report; dermatitis; female; human; intrahepatic cholestasis; pregnancy; pregnancy complication; pruritus; review